How Parents and Friends Influence Student Preference in Selecting a Bachelor’s Degree in Hotel and Tourism Management in Hong Kong - Grace Ho; Rob Law (Centre For Tourism Planning and Development, 2021)
This study looks at the decision-making in selecting a higher education programme from a consumer behaviour perspective and examines who influence students when making the decision on which hospitality and tourism Bachelor’s degree to pursue. Qualitative focus group interviews with current undergraduate students were conducted. The findings show that the most significant influencers are ‘friends and classmates’ followed by ‘family’ then ‘teachers’, while the cultural influence of Confucianism and collectivism might be the underlying basis for the decision process. Thus, higher education institutions can act accordingly based on these influences to achieve higher enrolment for their programmes.